Quantitative Estimation of Biocapped Surface Chemistry Driven Interparticle Interactions and Growth Kinetics of Gold Nanoparticles - Ahmad, T. (Springer, 2022)
In phytosynthesis of gold nanoparticles (AuNPs), biomolecules play a vital role in biocapping the surface of particles and generating the electrostatic repulsive forces to inhibit their growth kinetics. However, estimation of bioactive compounds influencing their surface characteristics through formation of electric repulsive forces (Velec), Van der Waals attraction forces (Vvdw) and ultimately hindering their growth is still in the phase of obscurity. Current study, based on surface chemistry approach has been performed for identification of bioactive compounds in Elaeis guineensis leaves (EGL/OPL), acting as biocapping agents and directing the growth of AuNPs over a period of time. The quantitative estimation of interparticle interactions and modification in Ostwald ripening (MOR) model were also done to correlate the growth kinetic of AuNPs. The X-ray photoelectron spectroscopy (XPS) showed the major contribution of oxygen, carbon and nitrogen elements, corresponding to polyphenolic, carboxylic and amides, in biocapping the surface of AuNPs and directing their interparticle interactions associated with growth kinetics. The Velec forces were reduced with an enhancement in the Vvdw forces, depicting their major role in impeding growth of AuNPs. The MOR model exhibited an excellent agreement of predicted growth with experimental size enlargements of AuNPs, having 4.8 average absolute relative percentage error. Â© 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.